2012
DOI: 10.1104/pp.112.203240
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Reduction of NADP-Malic Enzyme in Flaveria bidentis Reduces Flow of CO2 through the C4 Cycle  

Abstract: An antisense construct targeting the C 4 isoform of NADP-malic enzyme (ME), the primary enzyme decarboxylating malate in bundle sheath cells to supply CO 2 to Rubisco, was used to transform the dicot Flaveria bidentis. Transgenic plants (a-NADP-ME) exhibited a 34% to 75% reduction in NADP-ME activity relative to the wild type with no visible growth phenotype. We characterized the effect of reducing NADP-ME on photosynthesis by measuring in vitro photosynthetic enzyme activity, gas exchange, and real-time carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 38 publications
5
40
0
Order By: Relevance
“…4). NADP-ME influenced both the convexity and maximal CO 2 uptake rate of the A-C i curve, which is consistent with previous experimental observations (Pengelly et al, 2012).…”
Section: Control Properties Of Key Enzymes For C4 Photosynthetic Effisupporting
confidence: 81%
“…4). NADP-ME influenced both the convexity and maximal CO 2 uptake rate of the A-C i curve, which is consistent with previous experimental observations (Pengelly et al, 2012).…”
Section: Control Properties Of Key Enzymes For C4 Photosynthetic Effisupporting
confidence: 81%
“…1), suggesting that f can be maintained regardless of changes in A net . It has been demonstrated that A net is typically determined by total available energy, whereas f is determined by x (Siebke et al, 1997;von Caemmerer, 2000;Ubierna et al, 2011;Pengelly et al, 2012). Over time, the coordination of both cycles was achieved under all light qualities; however, the rate at which this balance was achieved differed between maize and M. giganteus.…”
Section: Discussion Light Quality and A Netmentioning
confidence: 99%
“…2c). It is difficult to disrupt this coordination through environmental perturbations, however molecular manipulations of F. bidentis by RNAi technologies have shown that reductions of Rubisco content disturbs the balance and leads to increased leakiness whereas reductions in C 4 cycle capacity through reduction in NADP malic enzyme reduces leakiness demonstrating that the balancing of biochemical capacities is important (von Caemmerer et al, 1997;Pengelly et al, 2012). However, it is puzzling that a different balance in the capacity of the carboxylases, i.e.…”
Section: Photosynthesis In Species With Kranz Anatomymentioning
confidence: 95%